2016
DOI: 10.1016/j.neuron.2016.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Genetic-Based Dissection Unveils the Inputs and Outputs of Striatal Patch and Matrix Compartments

Abstract: SUMMARY The striatum contains neurochemically defined compartments termed patches and matrix. Previous studies suggest patches preferentially receive limbic inputs and project to dopamine neurons in substantia nigra (SNc), whereas matrix neurons receive sensorimotor inputs and do not innervate SNc. Using BAC-Cre transgenic mice with viral tracing techniques we mapped brain-wide differences in the input-output organization of the patch/matrix. Findings reveal a displaced population of striatal patch neurons ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(207 citation statements)
references
References 63 publications
13
193
0
1
Order By: Relevance
“…Targeting of afferents to distinct striatal compartments such as patch and matrix may also differ between different cortical areas, though average sensorimotor populations target both patch and matrix neurons in similar proportions 56 . Afferents from both IT- and PT-type cells form connections to direct and indirect-pathway SPNs 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Targeting of afferents to distinct striatal compartments such as patch and matrix may also differ between different cortical areas, though average sensorimotor populations target both patch and matrix neurons in similar proportions 56 . Afferents from both IT- and PT-type cells form connections to direct and indirect-pathway SPNs 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Because information regarding the actual positions of these divisions is not currently available, they are only conceptually presented in schematic images of the striatum. Thus, even researchers using the newest technologies still do not have a common reference map that can be shared with others to facilitate mutual understanding of experimental data such as site-specific expression of genes (Tai et al 2013), virus-mediated detailed connectivity (Fujiyama et al 2011; Wall et al 2013; Smith et al 2016), and responses to channel-gating light with an illuminating apparatus placed in the brains of behaving animals (Valjent et al 2009; Friedman et al 2015; Smith et al 2016; Stephenson-Jones et al 2016; Bloem et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Afferents to patch and matrix are also thought to arise from different sources with patches receiving limbic inputs and matrix neurons receiving sensorimotor inputs (Gerfen, 1984). However recent viral tracing methods have cast doubt on this strict segregation (Smith et al, 2016). …”
Section: General Overviewmentioning
confidence: 99%
“…Another novel inhibitory projection from the bed nucleus of the stria terminalis to the striatum has also been described, terminating on patch and exo-patch SPNs in the dorsal striatum (Smith et al, 2016). Using tract tracing, another study identified an extrinsic source of acetylcholine arising from brainstem nuclei, the pedunculopontine nucleus and the lateral dorsal tegmental nucleus (Dautan et al, 2014).…”
Section: General Overviewmentioning
confidence: 99%